Qubit unitary lattice algorithm for spin-2 Bose-Einstein condensates: II - vortex reconnection simulations and non-Abelain vortices. Issue 1 (2nd January 2020) - Vahala, George; Soe, Min; Vahala, Linda
Abstract : Using the qubit unitary algorithm developed in the previous paper, quantum reconnection of non-Abelian quantum vortices is simulated and rung-like vortices are seen during the reconnection. Vortices in two of the four tetrahedral symmetry group are examined. Moreover, the algorithm performs exceptionally on classical supercomputers, as shown on timings on the IBM-Q supercomputer MIRA . It is expected that one should see the exponential speedup on a quantum computer since quantum entanglement is crucial for the qubit algorithm to recover the Gross-Pitaevskii equations for spin-2 systems.Keywords : spin-2 BECs, non-Abeliam vortices